Effective Assessment of Diabetes Control Using Personal Glucometers (CONTOURLINK, Bayer, Germany; CALLA, Wellion, Austria; LINUS, Agamatrix, USA). Issue 6 (19th December 2013) - Chlup, R.; Doubravova, B.; Bartek, J.; Zapletalova, J.; Krystynik, O.; Prochazka, V.
Abstract : Aim of this trial was to assess (1) the accuracy and precision of electrochemistry-based glucometers CONTOURLINK, CALLA, and LINUS and (2) the diabetes control using Ambulatory Glycaemic Profiles (AGP) as markers of therapeutic effectiveness. Glucometers and COBAS INTEGRA 400 Plus analyzer were used by one laboratory professional to estimate P-glucose (PG) in 112 out-patients. There were 112 sets of 12 PG estimations analyzed. In each set, means of 3 capillary PG estimations on 3 respective glucometers and on INTEGRA analyzer were calculated. The statistical program SPSS, v. 15, was applied. The mean INTEGRA PG values ranged from 2.7 to 25.3 mmol/L. There were strong correlations between mean PG on INTEGRA versus CONTOURLINK, versus CALLA, and versus LINUS; PG deviations from INTEGRA were mostly within the range ±15%. Wilcoxon Signed Rank Test revealed differences between CONTOURLINK-INTEGRA and LINUS-INTEGRA; CALLA-INTEGRA showed no difference. SD INTEGRA = 0.061 mmol/L, SD CONTOURLINK/SD CALLA/SD LINUS were 0.256/0.290/0.286 mmol/L. All patients were trained to perform defined 10-point PG profiles to adapt food, exercise, and insulin doses. The PG differences between all tested glucometers and reference values were in borderline of ISO 15197 but worthy of consideration. AGP are helpful markers of diabetes control.